Distributions of Lanostene-Derived Triterpenoids and Glucan Content in the Fruiting Bodies of the Australian Ganoderma Species - Aline De Oliveira Campos; Mark D. Harrison; David L. Marshall; Peter James Strong (Journal of Fungi)
Lanostene-derived triterpenoids and β-glucans are important metabolites in Ganoderma mushrooms associated with benefits to human health. The medicinal value of the Australian Ganoderma species remains unclear, with no data on triterpenoid distribution or glucan content. In the present study, 22 Australian Ganoderma specimens were analyzed for triterpenoid and glucan contents. Thirty-two triterpenoids were identified in the fruiting bodies of 19 of the specimens. Distinct patterns in triterpenoid distribution between laccate and matte fruiting bodies were observed, leading to the classification of four groups of Ganoderma. Most of the glucans in the Ganoderma fruiting bodies were β-glucans (~99%), with a nominal α-glucan content (~1%). The β-glucan content ranged from 19.5 to 43.5% (w/w). A range of antioxidant activities was observed for methanol extracts using the ABTS (1.8 to 8.4 mg GAE.g−1), DPPH (1.7 to 9.4 mg GAE/g−1) and FRAP (24.7 to 111.6 mmol FeSO4.g−1) assays, with four specimens presenting relatively high radical scavenging and reducing activities. For the first time, we demonstrated that Australian Ganoderma mushrooms contain medicinal triterpenoids, including ganoderic acid A, and we established a link between its distribution and the fruiting body morphology. However, further research is required to isolate diploid clones and determine factors that impact triterpenoid and glucan synthesis in these strains.